2005
DOI: 10.1161/01.cir.0000158665.27783.0c
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Blunts Endotoxin-Induced Tissue Factor In Vivo

Abstract: Background-Beyond lipid lowering, various antiinflammatory properties have been ascribed to statins. Moreover, in vitro studies have suggested the presence of anticoagulant effects of 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors, as lipopolysaccharide (LPS)-induced monocyte tissue factor (TF) was suppressed. In this study, we examined the role of statins in experimental endotoxemia on inflammatory and procoagulant responses in vivo. Methods and Results-In this double-blind, placebo-controlled, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 33 publications
2
80
0
4
Order By: Relevance
“…Simvastatin could attenuate lung damage after inhalational injury in mice, but only at high doses (47). In a doubleblind, placebo-controlled study, the endotoxin-induced systemic inflammatory response was reduced by preemptive simvastatin 80 mg in humans (48). Thus, our data are consistent with animal and human interventional studies of simvastatin.…”
Section: Original Articlesupporting
confidence: 82%
“…Simvastatin could attenuate lung damage after inhalational injury in mice, but only at high doses (47). In a doubleblind, placebo-controlled study, the endotoxin-induced systemic inflammatory response was reduced by preemptive simvastatin 80 mg in humans (48). Thus, our data are consistent with animal and human interventional studies of simvastatin.…”
Section: Original Articlesupporting
confidence: 82%
“…Statins are postulated to inhibit inflammation and coagulation 31,32 and to reduce TF expression and activity in blood monocytes and neutrophils. 20,33,34 Knowing that TF is a crucial mediator in pregnancy complications observed in CBA/J ϫ DBA/2 mice, we sought to investigate whether pravastatin can prevent pregnancy loss in this model of spontaneous miscarriages. In accordance with our hypothesis, pravastatin prevented fetal loss ( Figure 4A) and IUGR ( Figure 4B) in DBA/2-mated CBA/J mice at day 15 of pregnancy.…”
Section: Reduced Cell Proliferation Increased Oxidative Injury and mentioning
confidence: 99%
“…In addition, simvastatin blunted the increase of monocyte TF expression in response to lipopolysaccharides [2]. Other studies have suggested that statins can inhibit the production of proinflammatory cytokines [3].…”
Section: Statins: How Do They Work?mentioning
confidence: 87%